Competitive performance predictors in speed climbing, bouldering, and lead climbing - Winkler, M.; Künzell, S.; Augste, C. (Journal of Sports Sciences, 2023)
The study modelled the influence of anthropometric components, climbing-specific power, strength and endurance parameters, flexibility, coordination, and motor planning skills on competitive climbing performance in speed, bouldering, and lead climbing. Sixty-one competitive climbers (26 women [18.1 ± 1.9y], 35 men [21.4 ± 6.1y]) participated. PCA and MRA were used for statistical analyses. Significant predictors for speed climbing performance (R2 = 44% and 35%) were lower (ß = .43 and .47) and upper body power and strength (ß = .40 and .37) for women and men, respectively. For women`s bouldering performance (R2 = 39%), they were hip flexibility (ß = .42) and upper body power and strength (ß = .37), for the men`s (R2 = 53%) lower (ß = .41) and upper body power (ß = .41) and body fat (ß = .37). For women`s lead climbing (R2 = 58%) upper body power and strength (ß = .59) and finger endurance (ß = .48) predict performance, for the men`s (R2 = 58%) lower (ß = .36) and upper body power (ß = .28), body fat (ß = .27) and motor planning skills (ß = .27). The multivariate models provide a framework for scientifically grounded climbing training by emphasizing the role of specific performance components.